2005
DOI: 10.1016/j.rapm.2005.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A Description of the Spread of Injectate After Psoas Compartment Block Using Magnetic Resonance Imaging

Abstract: The most common pattern of injectate spread seen on MRI with both approaches to PCB was spread within the body of the psoas muscle around the lumbar branches (L2-4), with cephalad spread to the lumbar nerve roots. One catheter resulted in injectate between the psoas and quadratus lumborum muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 9 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…It can be considered that the increased distance between the injection site and the vertebral canal when an SIA is used may decrease the risk of a neuraxial distribution of the injectate. The epidural spread of a LA seems to be more closely related with the approach employed than to the volume of LA administered (Mannion et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It can be considered that the increased distance between the injection site and the vertebral canal when an SIA is used may decrease the risk of a neuraxial distribution of the injectate. The epidural spread of a LA seems to be more closely related with the approach employed than to the volume of LA administered (Mannion et al. 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the most common pattern spread was within the body of the psoas muscle around the lumbar branches (L2–L4) with cephalad spread to the lumbar nerve roots. One catheter resulted in injectate between psoas and quadratus lumborum muscles 28 . Biasi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have compared ultrasonography and MRI of the lumbosacral anatomy [30] and analyzed injectate spread with MRI [9, 31, 32]. The sensory mapping demonstrated segmental anesthesia from L2 to S1 in accordance with the perineural spread analyzed by MRI.…”
Section: Discussionmentioning
confidence: 87%